Islamic Mechanism for Conflict Management: A Feasible Antidote to World Crises - Akannni, Akanni Mukaila (KWASU Journal of Religious Studies, 2017)
It is an indubitable fact that there is proliferation of war and conflict throughout the world. In the North and South Korea, Sudan, Syria, Nigeria, Cameroon, etc. there is one conflict or the other militating against the peaceful co-existence of their people. The fundamental issues in dispute include but not limited to struggles among the cthnic peoples or religious ideologies for land or resources, social and economic power, and/or freedom and self-government. Some of these wars and conflicts have long-standing basis and are therefore very complicated. These complications, however, happened as a result of several key players participating in these conflicts, either overtly or covertly for selfish interests. The task of finding solutions to the conflicts seems to be the focus of UN- the most recognized international mediating organization, so that the world may live in relatively peaceful and harmonious state. However, the United Nations has been found wanting in proffering lasting solutions to these conflicts. This paper thus presents practicalised Islamic mechanism for conflict management as contained in the Qur’an and Sunnah of Prophet Muhammad.